The construction of femininity in Iceland - Annadís Greta Rúdólfsdóttir 1964- (1997)
A thesis submitted for a final examination for the degree of Doctor of Philosophy, Department of Social Psychology, London School of Economics and Political Science, University of London In this study it is argued that femininity is mediated by historical and cultural factors. I explore ow rapid changes in the social structure of Icelandic society have introduced challenges to many cultural constructions. The theoretical framework draws from the work of Michel Foucault, in particular the idea that the individual emerges through the practices and discourses s/he is constituted in, and that these incur power relations. Several entrance points have been selected into the Icelandic culture and its ideas of femininity. One is through a random sample of 209 obituaries, published from 1922 to 1992. The other is through semi-structured interviews with 18 women, aged 16 to 88, conducted in 1992. A discourse analysis reveals two dominant discourses for constituting the “Self”, with different implications for men and women respectively. “The discourse of the Soul” emphasizes the individual who puts others before herself, is selfless, obedient, dutiful and loyal. It is argued that these discourses were necessary for maintaining a particular power structure within the pre-modern Icelandic society, and that they portray particular roles as “natural”. Changes in modern Icelandic society have caused a rupture in the harmony between these discourses. New discourses have emerged, and women are increasingly putting their own needs and selves before others. The inter and intra-subjective tensions that these changes have incurred are traced. Women’s strategies of resistance that have unfolded in response to dominant ideas are outlined. In their different forms of disciplining sons and daughters, women use their position as mothers to encourage societial changes. Implications of these findings for theories of construction of femininity are discussed.